Analisis Efektivitas Platform SIAPKerja Dalam Transformasi Pelayanan Pembuatan Kartu Kuning (AK 1) dan Informasi Lowongan Kerja di Dinas Tenaga Kerja Kota Cilegon - Hilyah Maulidah; Gatot Hartoko; Ita Rosita Wahyiah (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Unemployment poses a significant challenge to the labor sector in Indonesia, including in Cilegon City. To enhance employment services, the Cilegon City Manpower Office has implemented the SIAPKerja Platform as a digital innovation for "Yellow Card" (AK-1) registration and the provision of job vacancy information. This research aims to analyze the effectiveness of the SIAPKerja Platform in transforming Yellow Card (AK-1) services and job vacancy information provision, identify implementation obstacles, and examine efforts to overcome them. The study employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which encompasses data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The research results indicate that the SIAPKerja Platform has improved service accessibility, speed, and efficiency, as well as staff adaptability and skills. The findings also show that service digitalization via SIAPKerja has reduced job seekers' reliance on face-to-face services; however, its utilization is not yet optimal due to limited access and digital literacy among some members of the public. Consequently, strengthening infrastructure, conducting broader outreach, and improving public digital literacy remain necessary. Overall, the platform contributes positively to the transformation of employment services in Cilegon City and supports the provision of inclusive, responsive, and sustainable employment services for residents.